Based on the molecular phylogeny of the genus Illadopsis, a very great genetic difference between sedentary populations of Illadopsis rufipennis resurrects the name Illadopsis extrema Bates, 1930 - Nguembock, Billy; Cruaud, Corinne (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Illadopsis rufipennis is a sedentary member of the African jungle babblers and in our paper concerning this group, we retrieved a strong divergence between its two subspecies. To check this divergence and leaning partially on our phylogram obtained in our paper already published, we investigated a genetic variation of the individuals of the two subspecies of Illadopsis rufipennis distributed in the West (Liberia) and the West (Central African Republic) of Africa. For this, we use two mitochondrial genes (ND2 and ND3) to calculate their genetic distances and to explore their mutational differentiation. We also used our phylogenetic as well as dating results already obtained and then some are already published. Thus with our ND2 and ND3, a genetic distance of 10.45% and 12.8% has been estimated respectively between individuals of Illadopsis rufipennis extrema (Liberia) and Illadopsis rufipennis rufipennis (Central African Republic) but it was, for the same markers, of 0.07% and 2.62% respectively between specimens of I. r. rufipennis caught in Central African Republic and Cameroon. For the mutational differentiation, a total of 153 different molecular characters have been observed on the two markers investigated between these two subspecies. Leaning on our dating results, the split between the subspecies Illadopsis rufipennis extrema (Liberia) and the subclade Illadopsis rufipennis rufipennis (Central African Republic and Cameroon) and Illadopsis pyrrhoptera was estimated at 2.98 Â± 0.88 Myrs. This time period coincide slightly with one of the three estimated peaks of the global cooling occurred in Africa which created and maintained forest refuges during this most arid period and plays a role in the speciation of several African taxa. Thus for these sedentary birds separated of around 3260 km with several geographic barriers, marked by the variation of the color of their top and sides of head as well as measures of their weight and for which no risk of recurrent gene flow is again possible, we suggest resurrecting name Illadopsis extrema Bates, 1930 for individuals referred as Illadopsis rufipennis extrema of this study.